Comportamiento agronómico de las hortalizas acelga (Beta vulgaris) y brocoli (Brassica oleracea) con dos abonos orgánicos en el Centro Experimental “La Playita” - UTC 2013 - Soria Proaño, Fredy Adrian (2015)
The survey was carried out in the Centre Experimental "La Playita" of the UTC following objective the evaluation of the agronomic performance of vegetables Swiss chard (Beta vulgaris) and Broccoli (Brassica oleracea l.), establish the behaviour and productivity of Chard and broccoli, the economic study of the organic production of vegetables in the town in study. A complete block design applied to random (DBCA) with four treatments and five replications for each vegetable and three plants as experimental unit. The major results in Chard: plant height in water hyacinth with 15,56 cm. to 30 days and 45 days with vermicompost 40,54 cm. length of sheet....